(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The objective of the present investigation is focused on the preparation of solid dispersions containing Nevirapine. The effect of various hydrophilic polymers on the aqueous solubility was studied. Kolliphor P188 was selected as carrier and solid dispersions were prepared by solvent evaporation technique. Evaluation of solid dispersion for percentage yield, drug content and solubility were most appropriate. Solid dispersions of drug: Kolliphor P188 and SLS (1:3:1 ratio) (SE9) shown higher dissolution rate i.e. 98.6% compared with and pure drug (37.5%) and other formulations. Powder X-ray diffraction performed on solid dispersion showed that Nevirapine existed in the amorphous form within the solid dispersion formulation fabricated using the solvent evaporation process. Additionally, scanning electron microscopy studies suggested the conversion of crystalline Nevirapine to an amorphous form. Therefore, the solid dispersions prepared by solvent evaporation method using Kolliphor P188 as hydrophilic carrier can be successfully used for improvement of solubility and dissolution of Nevirapine. Both in vitro dissolution testing and the in vivo studies demonstrated that the solubility and bioavailability of Nevirapine were significantly improved when formulated in a solid dispersion with Kolliphor P188 and SLS. The present study demonstrated that formulation of Nevirapine solid dispersion by solvent evaporation technique is a highly effective strategy for enhancing the bioavailability of poorly water soluble Nevirapine.